COMPOSITION OF THE COMMUNITIES OF OCTOCORALS AND CORAL PÉTREOS AND THE INCIDENCE OF THE BLEACHING OF 2005 IN JARDINES DE LA REINA, CUBA - Hernández-Fernández, Leslie (2011)
Octocoral and stony coral communities in the Jardines de la Reina archipelago (Cuba) were studied in 2001 and again in 2005.  The incidence of the 2005 bleaching event in the Caribbean was analyzed in the stony coral community. Twelve sampling stations were established: seven in the shallow forereef and five in reef crests, with one square meter quadrants to estimate density. A total of 62 species (26 octocorals and 36 stony corals) were identified in the shallow forereef, including Pseudopterogorgia americana (2.4 colonies/m2), Eunicea flexuosa (1.1 colonies/m2), Siderastrea siderea (5.0 colonies/m2) and Agaricia agaricites (4.0 colonies/m2). In the reef crest, 31 species were identified (13 octocorals and 18 stony corals), with Briareum asbestinum (1.3 colonies/m2), Porites astreoides (2.5 colonies/m2) and Millepora complanata (1.0 colonies/m2) being the most abundant. The most sensitive species to bleaching were: A. agaricites, Millepora spp. and Montastraea annulariS. In general, this event showed a poor incidence with stony corals. Constant monitoring is necessary to adjust the management plan to the changes that may occur in the structure of the benthic communities.